Moora's Method for Determining Preferred Pesticides for Rice Crops : Metode Moora dalam Menentukan Pestisida Pilihan Untuk Tanaman Padi - Rodesta, Nigel; Suryana, Febriyanno; Efendi, Raimon (Journal of Vocational Education and Information Technology (JVEIT), 2024)
The Jambak farmer group has difficulty in determining the preferred pesticide fertilizer because the decision-making process still uses manual methods, so the decision results are not precise and inaccurate. The purpose of this study is to help the Jambak farmer group determine the preferred pesticide fertilizer using the Decision Support system (SPK) with the Multi Objective Optimization on the basis of Ratio Analysis (MOORA) method, this method is able to optimize a number of different attributes simultaneously. This SPK system is implemented into the PHP programming language and MySQL database. The results of this study show that the best choice pesticide is Wingran with a total value of 0.2037. The use of this system can help the Jambak Farmers Group determine the preferred pesticide fertilizer appropriately and accurately.